Eutanasia dan Hak Asasi Manusia - Rospita A. Siregar (to-ra, 2015)
A patient who is suffering from terminal illness and an incurable condition has the possibility to propose to end his/ her life by lethal injection or suspending the medical treatment. This practice is known as euthanasia. Euthanasia is forbidden because it is categorized as homicide and consequently the perpetrator is punishable by criminal law. This reviewdiscusses (1) How is euthanasia legislation in Indonesian positive laws (2) How is euthanasia viewed from human rights perspective (3) How euthanasia is eligislated and conducted in some European countries. To analyze the afore mentioned problems, the writer conducts research by legal normative approach which is implemented in the thorough study of written regulation, official documents and related literatures. The writer finds tha Euthanasia is regarded as criminal act in Indonesia because it is a form of crime against life which stipulated in the Article 344 of the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/ KUHP):â€Anyone who takes life of others which is clearly done with an intention is punishable by imprisonment for maximum twelve yearsâ€. The Declaration of Human Rights has stipulated the â€œright to lifeâ€ which is fundamental and inherent in the nature of human being, universally acknowledge and an eternal endowment from The God. However, there are no any stipulations on-- the right to die and therefore euthanasia is a violation of human rights and against the principle of believing in one God. But, the right to die is already stipulated in some laws of developed countries, such as some countries in Europe